Conradian contracts : exchange and identity in the immigrant imagination - Juhász, Tamás, 1966- (Lexington Books, 2011)
This book treats Joseph Conrad's simultaneous interests in exchange, contracts, and the condition of displacement. The central hypothesis is that the novelist's characters face the option of signing or rejecting what might, with some generalization, be called a social covenant. These individuals conduct a lonely or marginal existence and, to ease their isolation, they would like to (re)enter a community. For this reason, they are ready to contribute to larger collective causes and comply with those restrictions that social life, in its contractual aspect, requires. As Julia Kristeva puts it, "